2020
DOI: 10.3390/ijms21031013
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Implicating Non-Dioxin-Like Congeners as the Key Mediators of Polychlorinated Biphenyl (PCB) Developmental Neurotoxicity

Abstract: Despite being banned from production for decades, polychlorinated biphenyls (PCBs) continue to pose a significant risk to human health. This is due to not only the continued release of legacy PCBs from PCB-containing equipment and materials manufactured prior to the ban on PCB production, but also the inadvertent production of PCBs as byproducts of contemporary pigment and dye production. Evidence from human and animal studies clearly identifies developmental neurotoxicity as a primary endpoint of concern asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 277 publications
(423 reference statements)
1
63
0
9
Order By: Relevance
“…This exposure reduced nose-to-nose interactions between males, but enhanced sociability and social approach in females and males [82]. In contrast, the four rats studies (three of which were performed in the same laboratory), demonstrated that perinatal exposures to either a mixture of PCBs 47 and 77 [84] or Aroclor 1221 [83,85,86] generally decreased sociability metrics in males and had mixed effects in females depending on the dose and timing of administration [73]. These observations are consistent with the sex bias of ASD; however, it is not possible to determine from these studies whether the effects are attributable to a specific mechanistic or structural subgroup of PCBs.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 87%
See 3 more Smart Citations
“…This exposure reduced nose-to-nose interactions between males, but enhanced sociability and social approach in females and males [82]. In contrast, the four rats studies (three of which were performed in the same laboratory), demonstrated that perinatal exposures to either a mixture of PCBs 47 and 77 [84] or Aroclor 1221 [83,85,86] generally decreased sociability metrics in males and had mixed effects in females depending on the dose and timing of administration [73]. These observations are consistent with the sex bias of ASD; however, it is not possible to determine from these studies whether the effects are attributable to a specific mechanistic or structural subgroup of PCBs.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 87%
“…While many of the earlier studies focused on the developmental neurotoxicity of legacy commercial mixtures, more recently, the neurodevelopmental impacts of individual PCB congeners or custom mixes based on PCB congener profiles documented in human tissues have been investigated. These studies are summarized in a recent review of animal studies published in the past decade that employed exposure paradigms relevant to humans, in terms of both the dose and exposure route [73]. The authors of the review concluded that the developmental neurotoxicity associated with exposures to legacy PCB mixtures is primarily mediated by NDL congeners.…”
Section: Neurobehavioral Effects Of Developmental Pcb Exposuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, PCBs continue to pose a significant risk to human health through exposure sources such as the continuous release from hazardous waste sites, PCB-contaminated equipment that is still in use, and contact with construction materials used in buildings erected prior to the PCB production ban. In addition, non-legacy PCB congeners have also been detected in paint and industrial pigments [ 186 ]. PCBs are still considered among the most important groups of food contaminants, and food and agricultural authorities strictly monitor the PCB contamination of foods.…”
Section: Cellular and Molecular Mechanisms Of Toxicity On Hematopomentioning
confidence: 99%